Contextualizing Muhammad Abduh’s Thought on Religious Tolerance in Indonesia - Nafakhati, Arfada; Fitria, Siti Nizarotul; Maulana, M. Fajar; Anbiya, Bakti Fatwa (Jurnal Pemikiran Islam, 2024)
Indonesia, characterized by its rich religious diversity, inevitably experiences variations in religious principles. Engaging in religious practices can sometimes lead to excessive fanaticism, resulting in conflicts and divisions within religious communities. To mitigate such challenges, fostering religious tolerance becomes crucial for promoting harmony. This qualitative research employs a library research method, analyzing secondary data sources to explore the concept of tolerance as interpreted by Muhammad Abduh, an Islamic theologian and reformist, in his work “Tafsir al-Manar.” Abduh’s interpretation aligns with Surah Al-Baqarah verse 256 from the Qur’an, emphasizing the importance of mutual respect and the freedom of belief without coercion. Given Indonesia’s context, where Islam is known for its openness, inclusivity, and problem-solving capabilities, studying and embracing the concept of tolerance from “Tafsir al-Manar” is highly relevant. The study concludes that Abduh’s perspectives on religious tolerance can significantly contribute to national harmony and the advancement of humanitarian values in Indonesia.